GEOPHYSICAL SURVEY FOR GROUNDWATER IN PART OF OBIO/AKPOR LOCAL GOVERNMENT AREA OF RIVERS STATE, NIGERIA - Owabie; W. Highpriest; Amonieah (Geological Behavior)
This research is aimed at carrying out geophysical survey for groundwater in parts of Obio/Akpo Local Government Area of Rivers State, Nigeria, using the Schlumberger electrode configuration of vertical electrical sounding (VES) technique. The field data were obtained using ABEM terrameter SAS1000 which was applied on eight VES location, a maximum distance of 300m current electrode spacing was used in the eight vertical electrical sounding points. Data acquired were interpreted using IPIN2Win 2022 version and Surfer13 softwares. The results obtained showed a 4-layers type A curve for Rumuepirikom and Rumuolumini VES locations, 5-layers type A curve for Rumuosi VES location, 4 and 5-layers type H curve for Ozuoba and Eneka VES locations respectively, 5-layers type K curve for Egbelu VES location and 4-layers type HK curve for Rukpoku and Rumuola VES locations. The apparent resistivity values range from 29.3344 – 252898.2075Ωm for Egbelu, 22.6195 – 674.0601Ωm for Rukpoku, 1.0631 – 230.9071Ωm for Rumuepirikom, 29.5833 – 600.8296Ωm for Rumuosi, 32.9867 – 561.5283Ωm for Rumuola, 29.0597 – 458.4212Ωm for Ozuoba, 29.0597 – 134.0413Ωm for Rumuolumini and 71.2094 – 338.1611Ωm for Eneka VES locations, and shows that Rumuepirikom and Rumuolumini are the most groundwater potential zones, thus will yield sufficient groundwater to wells, while Egbelu and Rukpoku are the least groundwater potential zones, thus will not yield sufficient groundwater to wells. The knowledge of this study can be applied in groundwater resources management, hydrological studies and regional town planning programs.